Handgrip strength values of Portuguese older adults: a population based study - Mendes, J (2017)
Background: Handgrip strength is used to identify sarcopenia and frailty phenotypes, being a potential predictor of mortality in older adults. However, uniformity is lacking in the reference values. This study aimed to describe handgrip strength values of older population aged >= 65 years in Portugal, considering the possible influence of anthropometric parameters. Methods: A cross-sectional study was conducted in Portugal, among 1500 older adults aged >= 65 years old, according to "The Nutrition UP 65 Study Protocol". Demographic data were collected and cognitive performance, subjective general health, physical activity, anthropometric parameters and nutritional status were assessed and analysed. Handgrip strength data was obtained with a Jamar dynamometer. A Pubmed/Medline search was carried out to compare handgrip strength data between Portuguese older adults and other older populations. Results: Handgrip strength was higher among men than among women (30.3 +/- 9.2 Kgf vs 18 +/- 5.4 Kgf, p < 0.001, respectively). In general, handgrip strength values of Portuguese older adults were lower than other older populations. In our sample, age, cognitive and nutritional status, self-reported sitting time and practice of physical activity were significantly correlated with handgrip strength in both sexes. Concerning anthropometric parameters, height was the most significantly correlated with handgrip strength (r = 0.34, p < 0.001, in women and r = 0.40, p < 0.001, in men). Conclusion: This study described, for the first time, handgrip strength values of Portuguese population aged >= 65 years, according to age and to sex-specific tertiles of height. The definition of handgrip strength reference values in this age group merits further reflection.